News Framing about Physical Construction in Jakarta Flood Management - Damayanti Wardyaningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The 2020 flood in Jakarta has brought people’s attention as it paralyzed the city’s activities. Different than other kinds of natural disaster like earthquake, tsunami, and mountain eruption, flood in Jakarta is a predictable event that could have been anticipated. In natural disasters, there should be a study to acquire the description of media coverage tendency toward the issue. The objects of this research are news published by Kompas (print media) during and post-flood disaster by using the framing method with four elements syntaxis, script, thematic, and rhetoric. The result suggested that news framing focuses no longer on the victims’ misery but on the comprehensive review with highlighted the rational argumentation flood handling from physical construction and resulted in meaningful information on mitigation effort so that natural events would not transform into disaster.